The Geography of Accessibility: Assessing the Malaysian Approach to COVID-19 Pandemic Management: Kebolehcapaian Geografi: Menilai Pendekatan Malaysia Dalam Pengurusan Pandemik COVID-19 - Fauziah, Che Leh (GEOGRAFI, 2020)
Several diseases, such as severe acute respiratory syndrome (SARS), influenza and Ebola, are epidemic-prone diseases that have threatened public health in the past. The coronavirus 2019 disease (COVID-19) outbreak, which started in Wuhan, China, in December 2019 and spread from there, was officially declared a public health emergency by the World Health Organization on January 30, 2020. Subsequently, COVID-19 was deemed a worldwide pandemic, as it had infected a large geographical area with a very high population density. As of 2 November 2020, more than 46,639,757 COVID-19 cases, and a total of 1,202,013 deaths, have been reported globally, and the number continues to grow. Therefore, an effective approach to public health policy is needed in most developing countries, including Malaysia, to facilitate preparation for and management of disease outbreaks in terms of health facilities, contact tracing and geographical access, at all levels of local and state governments. This article discusses an assessment of the Malaysian approach to the management of the COVID-19 pandemic, using secondary data obtained from the Malaysian Ministry of Health and online publications. The discussion shows that the introduction of technology to increase geographic accessibility will help in the management of the pandemic for all involved parties. Accessibility is an important indicator of disease control to a healthcare provider because it combines several factors, such as population, resources to access, source location and the distance between peoples’ residences and available resources.